2017
DOI: 10.1213/ane.0000000000002241
|View full text |Cite
|
Sign up to set email alerts
|

Preoperatively Screened Obstructive Sleep Apnea Is Associated With Worse Postoperative Outcomes Than Previously Diagnosed Obstructive Sleep Apnea

Abstract: Patients classified as S-OSA have similar rates of AREs to D-OSA patients, but increased postoperative respiratory interventions, hospital use, and 30-day all-cause mortality. These worse postoperative outcomes in S-OSA patients than D-OSA patients could reflect the lack of awareness and appropriate management of this bedside S-OSA diagnosis after PACU discharge. Multidisciplinary interventions are needed for these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…17 It must be noted that significant heterogeneity existed among the studies included in this analysis; it may be plausible that the association of STOP-BANG with respiratory complications was driving the pooled effect observed. More robust associations of STOP-BANG with respiratory complications have also since been exhibited, 29 although a recent prospective study found no predictive ability for postoperative hypoxaemia. 30 Our study, including only cardiac complications, did not find a significant adjusted association in these complications between the STOP-BANG risk strata.…”
Section: Discussionmentioning
confidence: 99%
“…17 It must be noted that significant heterogeneity existed among the studies included in this analysis; it may be plausible that the association of STOP-BANG with respiratory complications was driving the pooled effect observed. More robust associations of STOP-BANG with respiratory complications have also since been exhibited, 29 although a recent prospective study found no predictive ability for postoperative hypoxaemia. 30 Our study, including only cardiac complications, did not find a significant adjusted association in these complications between the STOP-BANG risk strata.…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive sleep apnea (Category B). Obstructive sleep apnea (OSA) and obesity hypoventilation syndrome (OHS) are highly associated with OIUAS and OIRD (Fernandez-Bustamante et al, 2017;Gupta et al, 2018;Kaw et al, 2012;Nagappa et al, 2017;Shin et al, 2016;Weingarten, Herasevich, et al, 2015). Patients diagnosed with OSA or those who screen positive for OSA using the STOP-BANG questionnaire (Table 3) and experience an opioidrelated respiratory arrest are more likely to experience a serious consequence such as anoxic brain injury and death (Fernandez-Bustamante et al, 2017;Fouladpour et al, 2016).…”
Section: Rationalementioning
confidence: 99%
“…ASA classification (Category B). When more than one comorbid condition exists, the likelihood of developing postoperative complication such as OIUAS and OIRD is increased (Fernandez-Bustamante et al, 2017;Gupta et al, 2018;Khelemsky et al, 2015;Lee et al, 2015;Pawasauskas et al, 2014;Rosenfeld et al, 2016;Schug, Palmer, Scott, Halliwell, & Trinca, 2016). For 50 years, anesthesia providers have used the American Society of Anesthesiologists (ASA) Physical Status Classifications system to rate a patient's risk of undergoing anesthesia (Hurwitz et al, 2017).…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations